PENGARUH PELATIHAN, KEMAMPUAN, KOMPENSASI, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA YANG BERDAMPAK PADA PRESTASI KERJA GURU PNS SMP NEGERI DI KOTA PANGKALPINANG - Sri Nurullita; Jumhanadi .; Adrian Radiansyah (LPPM STIE PERTIBA Pangkalpinang, 2017)
This research aims to analyze the effect of training, ability, compensation, communication and working environment to the working performance of either simultaneously or partially. Furthermore, to analyze the effect of the performance impacting on the achievement of the civil servant teachers in the Public Junior High School at Pangkalpinang City. There are 290 samples from 169 of the civil servant teachers in the Public Junior High School at Pangkalpinang City. The instrument of research using questionnaires, which are arranged in a scale 1-5. The score of 1 for very low response and score of 5 for an excellent response. The analysis method used is path analysis model of trimming (Path analysis). Hypothesis testing using the F test (simultaneous) and t-test (partial). The research concludes that there is a significant effect of the variable of influence of training, ability, compensation, communication and working environment either simultaneously or partially to the work performance and there is a significant effect on the performance variable to work achievement simultaneously and partially views of the determination coefficient of 48 percent